Students' Perception of the Development of a Digital Dictionary of Arabic Idioms Based on Corpus Linguistics - R.U., Nafisatul Izza; Mahliatussikah, Hanik; Ahsanuddin, Mohammad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The role of dictionaries in Arabic learning is vital, given their function in explaining terminology, improving information accessibility, and facilitating better communication and understanding. This study aims to analyze students' needs for a digital dictionary of Arabic idioms as a supporting means to improve student competence in written and oral aspects in the Department of Arabic Language Education, State University of Malang Undergraduate Program. The research method applied is descriptive qualitative, with a sample of 62 students, representing 14.69% of the total 422 undergraduate students of the Department of Arabic Language Education. Data collection was carried out through distributing questionnaires regarding the need for a digital dictionary of Arabic idioms. The results of the questionnaire analysis show the importance of developing the Al-Misbah dictionary as an additional tool that can enrich learning to speak and write Arabic in the lecture environment effectively. This dictionary is expected to help students understand the use of idioms better so that they can be applied appropriately in everyday life.